Problematic on Copyright Execution as Fiduciary Collateral When Debtor Defaults - Puspitasari Wardoyo, Yohana; Febriyan Praja Dewa, Andiko; Kharisma Nuryasinta, Radhityas; Luthfi, Muhammad; Ratna Indri Hapsari, Dwi (KnE Social Sciences, 2024)
The issuance of Government Regulation of the Republic of Indonesia Number 24 of 2022 on Regulation of the Implementation of Law Number 24 of 2019 on creative economy has served as the foundation of the copyright financing concept with an economic value, which can be used as fiduciary collateral. Therefore, problems that arose in the application of the mentioned concept are when copyright as fiduciary collateral is executed. Problem of copyright as fiduciary collateral for executed intellectual property due to defaulting debtor, which includes moral rights that remain attributed to despite the implementation of the execution, void of legal norms on the execution of copyrights and strength of minutes of auction evidence as proof of property rights transfer to copyright, as well as restriction of property rights by Law of Copyrights in the execution of copyright. Moreover, the research method applied in this paper was normative research, by analyzing library materials or primary and secondary data. The first result obtained only economic factors that are transferable in the transfer process of copyright, moral rights attributed to the creator, implementation of copyright execution such as legal objects with similar classification, and auction report as evidence of copyright transfer. Second, different restrictions from Article 28 H paragraph (4) of the 1945 Constitution of the Republic of Indonesia may lead to multiple interpretations and conflict of norms. The recommendation is to conduct a comparative study with countries that have the same legal system and revise Law Number 28 of 2014 on Copyright or establish the implementation of a mechanism for copyright execution. Keywords: problematic, copyright execution, fiduciary collateral